IMPLEMENTASI VIRTUAL LOCAL AREA NETWORK DENGAN SWITCH PORT PADA PT. MAXINDO MITRA SOLUSI JAKARTA (INTI Nusa Mandiri, 2020)
PT. Maxindo Mitra Solusi, is a company engaged in internet service providers (ISP) in the work of PT. Maxindo has many divisions, so it is necessary to divide the network segmentation from each division, requires one switch one division device so that it consumes a lot of the remaining switch ports and also purchases a lot of network devices, for that it is needed Implementation of network design that can divide network segments in a physical device. like a layer three switch. For the above problems, PT. Maxindo Mitra Solusi applies the concept of a Virtual Local Area Network (VLAN) with a manageable switch device that functions as a network divider between divisions, to help the Network Development process at PT. Maxindo Mitra Solusi uses the Network Development Life Cycle (NDLC) development method. VLAN implementation can facilitate network troubleshooting and maintenance, and become more organized in providing IP addresses, avoiding broadcast domains, increasing security and increasing network performance.
Keywords: VLAN; Switch; NDLC; Network Development Life Cycle